2013
DOI: 10.1097/mib.0b013e318281f336
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal Plexitis as a Predictor of Postoperative Surgical Recurrence in Crohnʼs Disease

Abstract: Early surgical revision and submucosal plexitis in proximal margins of ileocolonic resection specimens are independently associated with CD surgical recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
3
31
0
Order By: Relevance
“…Previous work failed to demonstrate that disease‐free proximal resection margins are a protective feature against the recurrence of inflammation; interestingly, our data indicated that increased density of S100‐positive EGCs in disease‐free margin is associated with postoperative recurrence. It has been found by several studies that plexitis was implicated in the postoperative endscopic, clinical, and surgical recurrence of CD . We demonstrated here for the first time that an increase in S100‐positive enterogial cells at a site devoid of inflammation may be predictor of postoperative disease recurrence.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previous work failed to demonstrate that disease‐free proximal resection margins are a protective feature against the recurrence of inflammation; interestingly, our data indicated that increased density of S100‐positive EGCs in disease‐free margin is associated with postoperative recurrence. It has been found by several studies that plexitis was implicated in the postoperative endscopic, clinical, and surgical recurrence of CD . We demonstrated here for the first time that an increase in S100‐positive enterogial cells at a site devoid of inflammation may be predictor of postoperative disease recurrence.…”
Section: Discussionsupporting
confidence: 60%
“…It has been found by several studies that plexitis was implicated in the postoperative endscopic, clinical, and surgical recurrence of CD. 11,15,29,41 We demonstrated here for the first time that an increase in S100positive enterogial cells at a site devoid of inflammation may be predictor of postoperative disease recurrence. This may partly explain that the extensive bowel resection is not protective from disease recurrence in anastomosis.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The Authors showed that early surgical revision after the first ileocecal resection (hazard ratio ¼ 9.56; 95% confidence interval, 2.02e45.19; P ¼ 0.0046), presence of submucosal plexitis (HR ¼ 8.02; 95% CI, 1.87e34.47; P ¼ 0.0054), and presence of more than 6 lymphocytes in the submucosal plexus (HR ¼ 5.84; 95% CI, 1.23e27.65; P ¼ 0.0269) were independently associated with risk of surgical recurrence. 81 …”
Section: Blood Transfusionsmentioning
confidence: 97%